Implementation of the business incubation program as an effort to accelerate the improvement of the quality of human resources in small and medium industries - Riza, Muhammad Faisal; Putra, Irfan Kharisma; Arif, Ahmad Bachtiar; Ngindana, Rispa (Universitas Islam Malang, 2023)
This research was conducted with the aim of improving and strengthening the quality of existing Human Resources in developing Small and Medium Industries (IKM), namely in the batik industry in Jatipelem Village, Diwek District, Jombang Regency. This research uses a qualitative approach with a case study method. The main problems found in this study are the absence of special design characteristics for Jatipelem batik, a lack of understanding of the concept of organizational management, a lack of capital for SMEs, the role of batik associations is not optimal, and digital sales are not optimal. The results of the study show that training and mentoring programs are needed in order to improve the quality of existing human resources, which include batik product design training, organizational management training, Business Model Canvas (BMC) training, IKM financial training, and digital marketing training.